Musa basjoo regulates the gut microbiota in mice by rebalancing the abundance of probiotic and pathogen. (June 2019) - Wei, Tao; Bao, Jin-Yong; Yang, Hai-Hua; Lin, Jun-Fang; Zheng, Qian-Wang; Ye, Zhi-Wei; Zou, Yuan; Li, Xiong; Jiang, Zhi-Le; Guo, Li-Qiong
Abstract: Musa basjoo is a kind of popular slimming fruit in southern China. However, even though the trophic component and physiological effect are well studied, its internal mechanism in reconstructing gut microbiota remains unclear. In this study, maturity of M. basjoo were divided into four levels. Results indicated that M. basjoo in level Ⅱ (with 35% maturity) represented the greatest increase in the growth in vitro of probiotics, Lactobacillus plantarum FMNP01 and Lactobacillus casei FMNP02. After feeding M. basjoo with the middle dose (2.67 g/kg·BW) to mice for 21 days, gut microbiota from mice feces was isolated and sequenced. Results of 16SrDNA sequencing showed that the scattered genera of gut microbiota were significantly gathered. The amounts of different pathogens were decreased, while probiotics such as genera Bacteroides and Roseburia were significantly increased ( p < 0.05). Results of function prediction indicated that the reconstruction of gut microbiota may due to the change in carbohydrate transportation, biosynthesis of cell wall, cell membrane, and cell envelope. This study has drawn a basic mechanism in reconstructing gut microbiota by feeding M. basjoo and lay out a foundation for further reach on the interaction between human as diner and M. basjoo as food. Highlights: Consistency of organs and weight of mice in all groups proved the food safety of Musa basjoo. The gut microbiota has been reconstructed by rebalancing the abundance of probiotic and pathogen. The reconstruction of gut microbiota might due to the change in carbohydrate transportation and synthesis of cell structure.